Can strategic environmental and social assessment of REDD+ improve forest governance? - Slunge, D.; Ekbom, A.; Loayza, F.; Guthiga, Paul M.; Nyangena, W. (University of Gothenburg, 2011)
The Forest Carbon Partnership Facility has recently proposed the application of strategic environmental social assessment (SESA) for incorporating environmental and social considerations in the preparation of REDD+ initiatives. This paper discusses the potential contribution of SESA to REDD+ initiatives drawing on experiences from earlier attempts to large scale forestry sector reforms and a recent World Bank pilot program on strategic environmental assessment. The paper suggests that SESA can be a useful approach for strengthening institutions and governance needed for managing diverse environmental and social impacts related to REDD+. More specifically, SESA can enhance policy making and governance through raising attention to environmental and social priorities, strengthening constituencies for policy change and improving social accountability. In order for SESA to contribute to these outcomes it needs to be assured that broad national “ownership” is achieved and that it becomes part of a long-term policy learning process with repeated and sustained stakeholder interaction. Through strengthening constituencies in policy reform SESA can potentially reduce the risk of regulatory capture of REDD+ by vested interests and make institutional checks and balances more effective. An analysis of Kenya's process of preparing a national REDD+ strategy is used to illustrate our case in the paper.